Strategi Guru dalam Membentuk Karakter Siswa melalui Nilai-nilai Kejujuran - Muhammad Munif; Fathor Rozi; Siti Yusrohlana (FONDATIA, 2021)
This study aims to analyze and examine the teacher's strategy in shaping the character of students through the values ​​of honesty. The research method used is a qualitative approach with field studies at SDN 3 Blimbing, Besuki, Situbondo. Collecting data in this study using observation and in-depth interviews. The data analysis technique is carried out with the stages of data collection, data reduction, data presentation, and drawing conclusions from research results. From this study, the results obtained are several teacher strategies that can be applied in school institutions including: teachers always start learning with the hadith of honesty, teachers always understand student achievement for students who have academic and non-academic achievements, teachers guide their students by implementing habituation attitudes and behavior honest in school, teachers are responsible for developing students' awareness of the importance of education, teachers apply a cooperative attitude to interact honestly at school. Implications in forming honest character, so far students have developed in terms of attitude, one of which is politeness in communicating, and being honest in conveying a message.